Il cerchio della paranoia politica. Possibili linee di frattura - Bazzicalupo, Laura (SocietàMutamentoPolitica, 2012)
Lacanian psychoanalysis can be used to reflect on the subtle and invisible processes of symbolic representation, in the context of stereotyping and dehumanization that we find in the paranoid style of politics (for example, in conspiracy theories). The article highlights such as the claim of self-conservative immunization is required for the process of political subjectification, but can produce a destructive reversal. In a paranoid communitarian identity, negativity is canceled and kakon projected on a persecutory Other. Last part of the article focuses on the nexus of paranoia and psycosis in the forms of gratuitous violence, terrorism and drugs, in post-totalitarian neoliberal system. Only the assumption of phantasy (that organizes our world view) and the crossing over or traversing it, can help open the circle of paranoid identity.